2009
DOI: 10.1124/dmd.108.026039
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide and Ciclesonide: Effect of Tissue Binding on Pulmonary Receptor Binding

Abstract: ABSTRACT:Newer inhaled glucocorticoids often show low systemic side effects because of their high protein binding. This study was interested in evaluating the effects of increased plasma protein and tissue binding on pulmonary receptor occupancy. Rats received des-ciclesonide (des-CIC; the active metabolite of the prodrug ciclesonide) and budesonide (BUD; a drug with lower protein binding but similar receptor affinity) as constant rate infusion over 6 h (intravenous bolus of 30 g/kg, followed by 10 g/h/kg over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…However, we used the free plasma concentrations as reference concentration by calculating the ratio of free tissue concentration to free plasma concentration, to easily capture differences in free tissue concentrations and compare them directly with free plasma concentrations. The lung was not included in the study to limit the experimental work, which had to be performed directly after the drug infusion, and as previous studies already showed that free concentrations of corticosteroids in lungs are similar to those in plasma (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we used the free plasma concentrations as reference concentration by calculating the ratio of free tissue concentration to free plasma concentration, to easily capture differences in free tissue concentrations and compare them directly with free plasma concentrations. The lung was not included in the study to limit the experimental work, which had to be performed directly after the drug infusion, and as previous studies already showed that free concentrations of corticosteroids in lungs are similar to those in plasma (23).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were performed using a commercial equilibrium dialysis cell (Pierce Biotechnology, Thermo Fisher Scientific, Waltham, MA, USA) using a cellulose membrane with 12-kDA cutoff under conditions suggested by the manufacturer and validated by Waters et al for a diverse set of compounds (22). Under these conditions, our in vivo results in mice (percent of unbound BUD in plasma and tissues; Table I) agreed well with those obtained in rats (plasma in mice: % unbound = 8.7-9.7, in rat: % unbound = 7.4; brain in mice: % unbound = 3.3-3.5, in rat: % unbound = 5.8; kidney in mice: % unbound = 1.2-1.5, in rat: % unbound = 2.6; liver in mice: % unbound = 2.7-3.2, in rat: % unbound = 2.0) (23). The comparison between rat and mice data seems feasible, as plasma binding of BUD was shown to be constant across a wide range of species (24).…”
Section: Equilibrium Dialysismentioning
confidence: 95%
“…The importance of protein binding on the efficacy of inhaled drugs has been recognized by Wu et al where the authors showed that glucocorticoids with higher plasma and tissue binding showed a reduced efficacy in the lung [61].…”
Section: The Need For Te Studies Once Pk Equivalence Is Demonstratedmentioning
confidence: 96%
“…10 Other approaches to measure tissue affinity include equilibrium dialysis or ultrafiltration of lung homogenates. 11,12 Homogenization of tissues has the disadvantage of disrupting the normal drug compartmentalization in the cells, including the pH differences, thereby precluding the possibility to study lysosomal trapping. The use of equilibrium dialysis or ultrafiltration of lung homogenates are not standard practices in pharmacokinetic/pharmacodynamic (PK/PD) evaluation of inhaled compounds because of the potentially large errors in the estimates of free drug concentration.…”
Section: Introductionmentioning
confidence: 99%